Nonparametric tests for common values in first-price sealed-bid auctions - Philip A. Haile; Han Hong; Matthew Shum (The Johns Hopkins University, Department of Economics, 2003)
We develop tests for common values at first-price sealed-bid auctions. Our tests are nonparametric, require observation only of the bids submitted at each auction, and are based on the fact that the winner's curse arises only in common values auctions. The tests build on recently developed methods for using observed bids to estimate each bidder's conditional expectation of the value of winning the auction. Equilibrium behavior implies that in a private values auction these expectations are invariant to the number of opponents each bidder faces, while with common values they are decreasing in the number of opponents. This distinction forms the basis of our tests. We consider both exogenous and endogenous variation in the number of bidders. Monte Carlo experiments show that our tests can perform well in samples of moderate sizes. We apply our tests to two di?erent types of U.S. Forest Service timber auctions. For unit-price (scaled) sales often argued to fit a private values model, our tests consistently fail to find evidence of common values. For lumpsum sales, where a priori arguments for common values appear stronger, our tests yield mixed evidence against the private values hypothesis.
Keywords: 330; first-price auctions; common values; private values; nonparametric testing; winner's curse; stochastic dominance; endogenous participation; timber auctions; Auktion; Nichtparametrisches Verfahren